(untitled) (Research, Society and Development, 2023)
Introduction: Frailty syndrome is characterized by reduced physical and cognitive reserves, making older people vulnerable to adverse events. This study describes a prototype sensor system developed for assessing frailty through physiological parameters and frailty markers. Methods: A prototype combining four sensors in network and a software package was developed and tested in four long-term care facility senior residents of both sexes, aged 60 and older, showing no locomotive syndrome or severe cognitive impairment. Three of them were frail and able to walk without aid (P1), holding onto the wall (P2) or with a cane (P3), and a non-frail participant (P4) walked without aid. Results: Regarding mean acceleration, P1 and P4 showed the lowest and highest values, respectively, on the antero-posterior axis; P4 had the lowest value on the medio-lateral axis; and P3 presented the highest value on the vertical axis. All participants showed similar roll angular velocity; P4 presented the lowest pitch angular velocity; and P1 and P4 had the highest mean yaw angular velocity. A sarcopenic participant (P2) exhibited the lowest force of muscle contraction. Conclusion: The device has potential to detect frailty markers for adverse outcomes in older people, such as postural instability and increased risk of falls.